Genetic Variants Associated with Sensitive Skin: A Genome-Wide Association Study in Korean Women - Seoyoung Kim; Kyung-Won Hong; Mihyun Oh; Susun An; Jieun Han; Sodam Park; Goun Kim; Jae Youl Cho (Life)
Sensitive skin (SS) is associated with discomfort, including burning, stinging, and itching. These symptoms are often exacerbated by environmental factors and personal care products. In this genome-wide association study (GWAS), we aimed to identify the genetic variants associated with SS in 1690 Korean female participants; 389 and 1301 participants exhibited sensitive and non-sensitive skin, respectively. Using a combination of self-reported questionnaires, patch tests, and sting tests, we selected 115 sensitive and 181 non-sensitive participants for genetic analysis. A GWAS was performed to identify the loci associated with SS. Although none of the single-nucleotide polymorphisms (SNPs) met the genome-wide significance threshold, we identified several SNPs with suggestive associations. SNP rs11689992 in the 2q11.3 region increased SS risk by approximately 3.67 times. SNP rs7614738 in the USP4 locus elevated SS risk by 2.34 times and was found to be an expression quantitative trait locus for GPX1, a gene involved in oxidative stress and inflammation. Additionally, SNPs rs12306124 in the RASSF8 locus and rs10483893 in the NRXN3 region were identified. These results suggest that the genetic variations affecting oxidative stress, cell growth regulation, and neurobiology potentially influence skin sensitivity, providing a basis for further investigation and the development of personalized approaches to manage sensitive skin.